Idiomatic Expression in ‘Fresh Off the Boat’ Series Released in 2015-2022 - Ayunda Permatasari; Yesika Maya Ocktarani; Yulia Mutmainnah (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
During the development of language use, English idiomatic expression is embodied in a conversation. This research aims to analyse the form and types of idiomatic expression in conversation. The object of this research is American sitcom series entitled “Fresh Off the Boat”. The sample of the research is season 5 and 6 that consist of 37 episodes.  The data of the research are the main character utterances that attach idiom on it.  This research followed Seidle and Mcmordie (1988) theory to analyse the form of idiomatic expression. To classify the types of idiomatic expression the researchers used O’Dell and McCarthy (2010) theory. To analyse the data, the researchers use descriptive qualitative method. After collecting the data, the researchers did data preparation, data reading, re-reading the data to confirm the data. Based on the data found, from 8 forms of idiomatic expression, there are only 7 forms. Those are 28 idioms with nouns and adjective, 3 idiomatic pairs, 38 phrasal verb, 33 verbal idiom, 34 idiom with key words from special categories, 11 key words with idiomatic use, and 14 idioms with comparison. According to the types there are 142 types of idiomatic expression, they are 12 simile, 2 binomial, 33 proverb, 40 euphemism, 39 cliché, and 16 fixed statements. Based on the type of idiomatic expression, euphemism is dominated the type of idiomatic expression in the series.